(untitled) (FLOVET - Boletim do Grupo de Pesquisa da Flora, Vegetação e Etnobotânica, 2023)
The expansion of agribusiness in Brazil challenges the future of traditional agricultural systems. This article intends to identify processes by which traditional farmers maintain agricultural diversity on the frontier of monocultures in the Brazilian Midwest, with ethnobotanical records of agricultural practices and agrobiodiversity with 86 quilombolas farmers in Baixada Cuiabana, resulting from production in spaces derived from cutting agriculture and burns. The crops are configured as islands of agrobiodiversity designed among cerrado fields, forests and fallow land, with the ingenious combination of cultural practices and production and conservation of creole and hybrid seeds in the face of the advance of capitalist agriculture. In these relatively stabilized territories, active agriculture is not yet threatened by commercial agricultural expansion or by the extraterritorial process of cultural disqualification. Valuing traditional territories are basic conditions to encourage farmers to continue conserving agrobiodiversity in a dynamic and cultural way over time and achieving the desired food sovereignty.